SYSTEMATIC LITERATURE REVIEW: PERAN KEPUASAN KERJA DALAM MEMEDIASI PENGARUH DESAIN ORGANISASI TERHADAP KINERJA PEGAWAI PADA INSTANSI PEMERINTAH - Diatul Amalia; Mawarni Putri Aulia; Rizky Fauziyah; Nuzulul Fatimah; Riyan Sisiawan Putra (GOVERNANCE: Jurnal Ilmiah Kajian Politik Lokal dan Pembangunan, 2026)
This study aims to provide a deeper analysis of the role of job satisfaction as a mediating variable in the relationship between organizational design and employee performance in government institutions. The research adopts a Systematic Literature Review (SLR) approach by examining ten scientific articles published between 2023 and 2025 from accredited SINTA and Scopus journals. The findings reveal that organizational design has a positive influence on job satisfaction, which is shaped by factors such as a supportive work environment, fair compensation systems, effective leadership, and internal organizational practices. Job satisfaction is also found to have a significant impact on employee performance, where employees with higher levels of satisfaction tend to be more productive, more committed, and more effective in completing their tasks. Furthermore, job satisfaction plays a significant mediating role in strengthening the relationship between organizational design and employee performance, indicating that the effect of organizational design on performance occurs not only directly but also indirectly through job satisfaction as an intermediary mechanism. Therefore, government institutions are encouraged to optimize organizational design while also paying attention to employees’ psychological well-being in order to improve performance and the quality of public services.